Ovarian cycle, reproductive performance and breeding seasonality of Amazonian yellow-footed tortoises (Chelonoidis denticulatus) in the wild - Pedro Mayor; Sara Hidalgo; Hani R. El Bizri; Thais Q. Morcatty (Theriogenology Wild, 2023)
Studies of the reproductive functional morphology of chelonians are important to understand the reproductive physiology, anatomy, and endocrinology of these species. However, data on the reproduction of this group have been difficult to obtain because of their cryptic habits and as a result the consequent inefficiency of conventional field methods in detecting individuals in the wild. In this study, we obtained reproductive organs from 347 adult female yellow-footed tortoises (Chelonoidis denticulatus), one of the most hunted and traded land vertebrates in South America, donated by local sellers in a wild meat market in the Peruvian Amazon. We described the species’ reproductive cycle and the influence of climatic factors on reproductive performance. Of the sampled females, 116 (33.4%) were gravid and 231 (66.6%) were non-gravid, including 215 vitellogenic (62.0%) and 16 non-vitellogenic (4.6%). The mean number of ovarian follicles per female declined from 28.5 (<10 mm diameter), to 7.1 follicles (20–40 mm) to 3.2 follicles> 40 mm. Gravid females had in average 3.7 shelled eggs in the oviduct, with a mean egg diameter of 53.7 mm. The estimated annual reproductive potential in gravid females was 5.1 eggs per clutch, ranging from one to 22 eggs. There was a strong positive relationship between the diameter of shelled eggs and the straight carapace length of gravid females. The final phase of the folicular growth, the most demanding energetic process in chelonian reproduction, correlated with annual rainfall peak, while oviposition was estimated to occur in the dry season. The yellow-footed tortoise should be considered an opportunistic seasonal breeder, though capable of reproducing throughout the year. Reproductive yields are linked to climatic events that influence food availability in the environment. To improve the sustainable use of this species, adult females should be harvested primarily during reproductive quiescence, from the end of the laying period in the late dry season to the mid-rainy season when large follicles appear, to avoid taking gravid females. Our results are useful not just to better understand the reproductive biology of terrestrial chelonians but can inform the conservation management of harvested species.